2005
DOI: 10.1515/cclm.2005.156
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteins profile as an indicator of malignancy: multivariate logistic regression and ROC analyses

Abstract: The electrophoretic pattern of serum proteins of 85 patients carrying different types of neoplasia and 85 matched healthy adults were comparatively studied by agarose gel electrophoresis, to find out if there is a specific protein pattern common to different types of cancer. Each protein fraction was analyzed quantitatively by densitometry. Multivariate logistic regression and receiver operating characteristic (ROC) analyses were performed using SPSS software. When total protein and albumin were measured by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
6
10
0
Order By: Relevance
“…Growing tumors induce hypoalbuminemia via secreting in ammatory cytokines, which may inhibit albumin synthesis and promote albumin loss, resulting in weak systemic response. Rasouli et al [29] reported that patients with malignant tumors had a decreased concentration of albumin, which were measured by colorimetric methods, compared with healthy controls, which was accordant with the present study results. Globulin, as a re ector for most proin ammation protein, was increased by the accumulation of acute-phase proteins and immunoglobulins [30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Growing tumors induce hypoalbuminemia via secreting in ammatory cytokines, which may inhibit albumin synthesis and promote albumin loss, resulting in weak systemic response. Rasouli et al [29] reported that patients with malignant tumors had a decreased concentration of albumin, which were measured by colorimetric methods, compared with healthy controls, which was accordant with the present study results. Globulin, as a re ector for most proin ammation protein, was increased by the accumulation of acute-phase proteins and immunoglobulins [30].…”
Section: Discussionsupporting
confidence: 93%
“…The AGR, which is compatible with hypoalbuminemia and hyperglobulinemia, may be able to more accurately re ect the nutritional and in ammatory state, and thus, is associated with the progression of neoplasia. The electrophoretic data of serum proteins showed that the AGR was signi cantly decreased in 85 patients harboring cancer relative to controls [29]. Cheng et al [31] con rmed that the globulin-to-albumin ratio (GAR), was signi cantly higher in the subjects with liver disease compared with individuals with no evidence of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins are important building blocks of cells, tissues and vital for body growth, development and health (RASOULI et al, 2005). In the present study, total proteins and albumin were significantly decreased in mice of G3 (irradiated at 0.8 Gy) and in mice of G6 (malignant -irradiated at 0.8 Gy) this decrease in total protein in both two groups might be referred to the effect of radiation which may be leads to damage of vital biological processes or to changes in permeability of liver, kidney and other tissue cells leading to leakage of proteins via the kidney (CHOLDHARI;CHAKRABARTI, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to acute-phase proteins, red blood cell aggregation is increased by immunoglobulins. Presence of cancer cells in the body may stimulate an immune response from the host, thereby increasing the level of acute-phase proteins and immunoglobulins (4). Moreover, some hematologic cancer cells themselves may produce immunoglobulins that are excreted in the blood; that is, in multiple myeloma and Waldenstrom's macroglobulinemia.…”
Section: Introductionmentioning
confidence: 99%